Building resilience through urban commons: A policy recommendations for atomic shelter management - Antonija Bogadi (Tehnički Glasnik, 2017)
This paper presents set of arguments for incorporating urban commons as a way to increase resilience of the city. Vacant fallout shelters in residential neighborhoods are suitable case study, i.e. type of public place which could benefit from establishing commons management regime. Based on literature review on urban commons and site analysis, policy recommendations for developing urban commons on those sites are focused on needed actions from the local government and other stakeholders in "commons associations". Assigning bundles of rights to local user groups in order to stimulate self-organizing and long-term investments in active place management is a precondition for an urban common to succeed. The work presented here has implications for future studies of applicability of urban commons.